High-Sensitivity Toxic Gas Sensor Utilizing Photonic Crystal Fibers in the THz Spectrum - Mir Sabbir Hossain; Ariyan Haque Joy; Diponkar Kundu; A. H. M. Iftekharul Ferdous; Abdullah Al Mamun; Md Jakir Hossen (Emerging Science Journal)
SO2, HCN, and Cl2 gases are extremely toxic and can present significant health hazards even at minimal amounts, including respiratory and neurological systems. Timely identification aids in averting exposure and alleviating possible health risks, particularly in industrial and densely populated regions. Moreover, these gases can contribute to environmental pollution; thus, their monitoring is essential for human safety and environmental preservation. This specification recommends employing a photonic crystal fiber (PCF) to construct a terahertz octagonal core and curved air hole sensor for the detection of SO2, HCN, and Cl2 in the THz region. We routinely evaluate the recommended framework numerically, utilizing the entire finite element method. In terms of Cl2, the recommended sensor has a larger numerical aperture of 0.2909 and a superior sensitivity of 99.58%. Furthermore, this simulation yields a reduced effective material loss equal to 0.0020 cm-1 with a 3.094×10-12dB/m confinement loss for this gas. This technology utilizes the distinctive interaction between THz vibrations and gas molecules, improving detection sensitivity at trace levels relative to other techniques. This type of sensor may have practical applications in chemical sensing, biosensing, and gas sensing.